CURRENT SITUATION AND PERSPECTIVES OF REGIONAL INSTITUTES OF DEVELOPMENT IN THE RUSSIAN FEDERATION. (TULA REGION) - F. Sharipov; R. Ravilova; P. Sheyka (Вестник университета)
The article focuses on vital problem of improving the business climate and creating the most favorable conditions to attract investors in the Russian Federation regions. Establishment of specialized organizations is being analyzed for the promotion of investments on the basis of the principle «one window» (institutes of the regional development) taking as an example Tula Region Development Corporation. Identified the key problems of regulation of the institutes of the regional development and proposal for the further prospectives of this kind of institutions is given.